Menelusuri Hakikat Pembelajaran Dalam Islam Dari Rasulullah Hingga Ulama Klasik Dan Modern - Linda Asmaraneti; Reni Puspita; Hilmin Hilmin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research discusses how learning in Islam started from the time of the Prophet to the time of classical and modern ulama. This article explores the nature of learning in the Islamic context from a historical perspective, focusing on the role of the Prophet as the main learning model and the expansion of the legacy of knowledge through classical and modern scholars. Exploring the nature of learning in Islam provides a deep understanding of how religious values ​​and knowledge can complement each other. By analyzing the journey of learning from the Prophet to classical and modern scholars, it can be understood that an inclusive approach to learning is the key to maintaining the relevance of Islamic teachings in various eras. The literature study research method is a relevant approach in tracing the nature of learning in Islam from the time of the Prophet to the era of classical and modern ulama. In this method, researchers examine and analyze various literary sources which include literary works, scholarly writings, history and philosophical views that have existed throughout Islamic history. As for the results of this research, it can be seen that since the time of the Prophet, education has been the main focus in Islam, with teaching and learning considered the main way to understand and appreciate religious teachings. Classical scholars such as Imam Al-Ghazali and Ibn Sina played a key role in formulating an educational framework that combined science with Islamic values. They established a strong foundation for learning in the Islamic tradition. In the modern era, Islamic scholars and scholars continue to try to reinterpret the concept of learning in the current context, trying to bridge the gap between traditional values ​​and the demands of the modern world.